Elective preterm birth for fetal gastroschisis (Review) - Grant, Natalie H.; Dorling, Jon; Thornton, Jim (Wiley, 2013)
Background: Gastroschisis is an uncommon congenital defect of the interior abdominal wall that results in herniation of intestinal loops outside the abdominal cavity. Babies with gastroschisis generally do well, but there remains a mortality rate of 5% to 10% and some require prolonged parenteral nutrition and intensive care. Significant injury to the exposed bowel may occur in-utero, and earlier birth may reduce this, improve long-term outcomes and reduce complications, such as necrotising enterocolitis. However, it may also increase complications related to prematurity. There is a lack of published data in this area.